A Taste of Communists' Own Medicine: The Political Consequences of Land Reforms in Japan and Taiwan - Daniel Minghan Chiang; Elliott Fan; Dexter Hsu (Institute of Labor Economics (IZA), 2025)
Postwar land reforms in East Asia were implemented as a geopolitical strategy to curb communism expansion. This paper evaluates their long-term political effects in Japan and Taiwan. In Japan, reform increased support for conservative parties and reduced backing for socialist and communist factions, with intergenerational persistence. Taiwan's reform similarly bolstered electoral support for the Kuomintang. IV analyses support a causal interpretation. Survey evidence suggests that land acquisition fostered a desire for political stability as the mechanism, rather than through reciprocity or pro-market ideology. These findings highlight land reform's critical role in shaping postwar political alignment and deflecting communist influence.
Keywords: Q15; Q11; N55; P26; 330; land reform; communism; Japan; Taiwan